How to Develop Pak-China Relations in the Post Pak-India Conflict: How China Can Help Pakistan: https://doi.org/10.5281/zenodo.16875144 - Imraz Muhammad; Zahir Zada; Seema Zaheer (`, 2025)
A multifaceted strategy, including favored economic cooperation, diplomatic and political cooperation, defense and strategic partnership focus, technical collaboration, and territorial integration is necessary to improve Pakistan-China relations in the wake of the Pak-India conflict. India is a growing Asian force that is pro-Western, which could pose security and economic problems for China as well as Pakistan. Pakistan faces new competitive dynamics as a result of India's defense expansion and technological developments, but its weak economy makes it more difficult for it to establish a balance of power with India. In the meantime, Pakistan's economic and security environment, as well as regional stability, are significantly impacted by the Pak-India conflict. In this regard, bolstering Pakistan-China ties might be extremely important for advancing Pakistan's security and development goals. Examining how to improve relations between China and Pakistan in the wake of the conflict between India and Pakistan is the primary goal of this research project. And how can China assist Pakistan? Keywords: Strategic Partnership, CPEC, Security Cooperation, China and Pakistan.